ANALISIS IMPLEMENTASI PROGRAM JAMINAN PERSALINAN DI PEMERINTAH DAERAHKOTA TANJUNGBALAI TAHUN 2019 - Heri Rahman; Matius Bangun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
Law of the Republic of Indonesia No.36 of 2009 concerning Health, article 17 paragraph 1 states that the government is responsible for the availability of access to information, education and health service facilities, one of which is the Maternity Insurance Program (Jampersal). This is what researchers do about how it is implemented in the Municipality of Tanjungbalai, North Sumatra. Implementation evaluation is carried out on the objectives, accountability and input provided for improvement in the future. The results showed that the implementation of childbirth insurance in Tanjungbalai City has not been running optimally so it needs improvement in the future both in structural synergy, namely the relationship between central and regional as well as in harmony, namely functionally between other related agencies in the Tanjungbalai City Government. From the SWOT analysis carried out, namely analyzing the Internal Strengths and Weaknesses and the External Opportunities and Threats factors, it shows the position of the Tanjungbalai City Government is in Quadrant I (first) with an Aggressive Strategy, namely using existing strengths to take advantage of the opportunities available.